Analisis Nilai Heroisme dan Nilai Pendidikan Spiritual Pada Novel Segala Yang Diisap Langit Karya Pinto Anugrah dan Pemanfaatannya Sebagai Bahan Ajar Bahasa Indonesia di SMA - Aditya Pratama; Nanang Maulana; Henri Henriyan Al Gadri (Universitas Mathla'ul Anwar Banten, 2025)
This study aims to analyze the values of heroism and spiritual education in the novel *Segala yang Diisap Langit* by Pinto Anugrah, as well as its utilization as teaching material for Indonesian language in high school. This research uses a qualitative method with a descriptive approach, where data is obtained through content analysis of the novel's text. The results show that this novel contains various values of heroism such as love for the homeland, hard work, patriotism, appreciation, love of peace, responsibility, and friendship, as well as values of spiritual education that include the formation of attitudes, mentality, inner self, feelings, and awareness. These values align with the objectives of character education in the Merdeka Curriculum because they can foster moral, spiritual, and humanitarian spirit in students. Thus, the novel *Segala yang Diisap Langit* not only has literary aesthetic value but is also relevant to be used as teaching material that supports character development. strengthening religious values and the holistic development of students' personalities